Back Cover: Ceria‐Supported Gold Nanoparticles as a Superior Catalyst for Nitrous Oxide Production via Ammonia Oxidation (Angew. Chem. Int. Ed. 19/2022). Issue 19 (28th March 2022) - Tang, Zhenchen; Surin, Ivan; Rasmussen, Asbjörn; Krumeich, Frank; Kondratenko, Evgenii V.; Kondratenko, Vita A.; Pérez‐Ramírez, Javier
Abstract : A game of two halves Direct ammonia oxidation unlocks a pathway towards affordable and efficient production of nitrous oxide, a highly promising agent for selective oxidation reactions, but necessitates the development of suitable catalysts. In their Research Article (e202200772), Javier Pérez‐Ramírez and co‐workers demonstrate that the synergistic interaction between Au nanoparticles and CeO2 support results in a material with unprecedented levels of N2 O selectivity and productivity, far surpassing state‐of‐the‐art systems.